PENGARUH PROMOSI PRODUK, KETERSEDIAAN BARANG, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI DEALER ASTRA MOTOR NEGARA - I Kadek Putra Swintara; Helena Ni Gusti Ayu Putu Pusparini; I Komang Sudarsana (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to determine and analyze the partial and simultaneous influence of product promotions, product availability, and prices on consumer purchasing decisions at Astra Motor Negara Dealers. This study was conducted from October 2025 to April 2026. The research method used was quantitative. The population in this study included all active consumers who purchased Honda brand spare parts in 2022 with a total of 4,413 people. Sampling was carried out using a non-probability sampling technique with a purposive sampling approach, which designated 33 permanent employees as respondents. Data analysis was carried out using multiple linear regression through SPSS version 23 software. The results of partial testing (T Test) showed that Product Promotion t-count = 5.163, Product Availability t-count = 19.669, and Price t_count = 9.856 each had a positive and significant effect on Purchasing Decisions. Simultaneously (F Test), the third variable has a positive and significant effect on Purchasing Decisions with an F-count value of 716.327 (p < 0.05). Furthermore, Goods Availability is identified as the most dominant variable influencing consumer purchasing decisions with a standardized beta coefficient value of 0.543. Therefore, the following conclusion is drawn, namely Product promotion has a positive and significant effect on Purchasing Decisions at Astra Motor Negara Dealers. For further researchers, it is recommended to add other variables that can influence purchasing decisions, such as service quality, brand image, location, or consumer satisfaction so that the research results become more comprehensive.